Culture Teaching in Historical Review: On the Occasion of ASOCOPI's Fiftieth Anniversary - Bryan Meadows (Asociación Colombiana de Profesores de Ingles, 2016)
This literature review surveys fifty years of English language teaching scholarship on the topic of culture teaching. The review segments the available literature according to decade and applies two guiding questions to each resource found: How is culture defined and What does culture teaching look like. The report of findings details how authors in each decade literature set define culture and culture teaching. Discussion of the findings offers general observations of developments as well as consistencies over the entire literature set (1965-2015). This literature review will be of interest to current and emerging English language teaching scholars involved in culture teaching scholarship. It is dedicated to ASOCOPI's fifty-year anniversary (1965-2015).